Efektivitas Penerapan Sistem dan Prosedur Akuntansi Aset Tetap pada Dinas Perhubungan Kota Medan - Indira Indah; Syafrida Hani (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effectiveness of the implementation of fixed asset accounting systems and procedures at the Department of Transportation of Medan City. The research employs a qualitative approach with a descriptive method to gain an in-depth understanding of actual field conditions. Data were collected through observation, interviews, documentation, and literature review, involving four informants directly engaged in fixed asset management. The results indicate that the implementation of fixed asset accounting systems and procedures has been relatively effective, as reflected in the execution of asset management stages in accordance with applicable regulations and the utilization of information technology-based systems. These systems support more structured recording and reporting processes. However, the effectiveness has not been fully optimized due to several constraints encountered during implementation. Factors influencing effectiveness include the quality of human resources, the use of technology, data completeness, and coordination among work units. The identified challenges involve data inaccuracies, limited user competence, weak internal control, and technical issues within the system. These conditions affect the quality of financial reports, particularly in terms of accuracy and timeliness, and also influence the effectiveness of internal control. This study contributes by identifying key issues and highlighting the importance of improving system quality and human resource capacity to support more effective and accountable fixed asset management.